Hubungan Antara Jenis Kelamin Dengan Angka Kejadian Dermatitis Seboroik - Eka Silvia; Anggunan Anggunan; Arif Effendi; Isma Nurfaridza (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Background : The incidence of seborrheic dermatitis is related to several risk factors, one of them is gender. Men have a two times greater incidence than women, associated with androgen hormone stimulation, resulting in sebaceous activity to produce more sebum. Increased sebum can induce Malassezia proliferation and trigger seborrheic dermatitis. Purpose : To determine the correlation between gender and incidence rate of seborrheic dermatitis in dermatovenerology polyclinic of regional general hospital dr. H. Abdul Moeloek Bandar Lampung 2019. Method : Using an observational analytical design with a cross-sectional approach. The samples were collected by using total sampling technique. Data collection was done by recording in medical records and registration books and then analyzed them using the Chi-Square test. Results : There were 217 samples collected. There were 52 male patients (63%) and 31 female patients (37%) with dermatitis seborrheic, while in atopic dermatitis based on gender, 58 male patients (43%) and 76 female patients (57 %) were found. Chi-Square statistical test results obtained p = 0.008 (p <0.05) which meant a significant correlation between gender and incidence rate of seborrheic dermatitis. Conclusion : The final results show that the male sex, has a greater risk to trigger seborrheic dermatitis.